2015
DOI: 10.1080/09593330.2015.1010594
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasonic waves on the removal of different oil components from oily sludge

Abstract: (2015) Influence of ultrasonic waves on the removal of different oil components from oily sludge, Environmental Technology, 36:14, 1771-1775, DOI: 10.1080/09593330.2015 Ultrasonic technology is a promising tool for washing oily sludge to recover oil. In this study, the influence of ultrasonic conditions on the removal of different oil components from oily sludge was investigated to optimize ultrasonic washing technology. Among the three frequencies (25, 50 and 100 kHz) applied, ultrasonic washing at 25 kHz e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Ultrasonic technology is a promising clean methodology for treating oily sludge to recuperate oil. Indeed, several works have been conducted concerning this issue (Gao et al 2015 ). In order to improve the ultrasonic treatment protocol, it was investigated how ultrasonic circumstances affected the separation of various oil components from oily sludge.…”
Section: Processing Of Oleaginous Depositsmentioning
confidence: 99%
“…Ultrasonic technology is a promising clean methodology for treating oily sludge to recuperate oil. Indeed, several works have been conducted concerning this issue (Gao et al 2015 ). In order to improve the ultrasonic treatment protocol, it was investigated how ultrasonic circumstances affected the separation of various oil components from oily sludge.…”
Section: Processing Of Oleaginous Depositsmentioning
confidence: 99%
“… Application Reference Study Overview CO 2 flooding Wang et al [95] US application for oil–gas miscibility during CO 2 flooding and extraction of tight oils Hamidi et al [36] US-assisted CO 2 flooding in a porous media, parameters optimization incl. temperature Enhanced diffusion of colloids Yeh and Juarez [102] US application for colloidal particles mobility increase of in porous media EOR Qajar et al [78] Effect of US and solvent treatment on heavy oil rheology and asphaltene structure Abdulfatah [1] US as EOR using Niger Delta crude oil Agi et al [10] Acoustic parameters study for recovery of kerosene and paraffin Arabzadeh and Amani [20] US as EOR by means of free fall gravity drainage Mohsin and Meribout [62] Model for US as EOR Naderi and Babadagli [70] Immiscible displacement processes under US waves Najafi [71] US as EOR by means of free gravity drainage EOR from sludges Lins et al [53] Study of US treatment combined with mechanical stirring for oil recovery from waste lubricant oil Luo et al [55] Effect of US treatment on oil recovery from oily sludges He et al [37] US parameters study on EOR from sludges Gao et al [27] US waves on the oil components removal from oily sludge Formation damage Otumudia et al [75] Effect of ultrasound in removing plugging using glass models to simulate oil reservoirs Ghamartale et al [29] Permeability and pore structure enhancement using US Wang and Huang [96] Water-induced dama...…”
Section: Us In Enhanced Oil Recoverymentioning
confidence: 99%
“…Removal rates of up to 60 % and oily sludge contents of 42 % were achieved, with the possibility of further improvement by the addition of surfactants. In 2015, Gao et al [27] also investigated the removal of different components from oily sludge using ultrasonic treatment. Applying frequencies between 25 and 100 kHz, results showed that optimal ultrasonic washing performance in terms of oil extraction rate and efficiency was observed at 25 kHz.…”
Section: Us In Oil Recovery From Sludges Wastewater Tar or Oily Sandsmentioning
confidence: 99%
“…The optimal conditions for these parameters must be determined. The optimum conditions for oil sludge treatment for frequency, intensity, power, and soil-to-water ratio are 25 kHz, 0.33 W/ Cm 2 , 300 W, and 1/2, respectively [34]. With increasing temperature, the viscosity of the crude oil and the adhesion stress between the oil and the sand decrease.…”
Section: Figurementioning
confidence: 99%